Cars out of place : Vampires, technology, and labor in East and Central Africa - White, Luise (My University, 1993)
This essay is about things that never happened. The African vampires discussed here are not the undead, but men and occasionally women specifically employed--as firemen in East Africa and game rangers in Central Africa--to capture Africans and extract their blood. Such vampires were said to exist throughout much of East and Central Africa; they were a specifically colonial phenomena and were first noted in the late 'teens and early 1920s. In the colonial versions of these stories, most vampires were black men supervised on the job by white men, but in postcolonial versions who works for whom has become unclear. Although it seems plausible that these stories originated in botched medical procedures done in too great haste during World War I, establishing their source does not account for their meaning thirty years later, or their power, or the passion with which they were retold and withheld. Stories in which colonial employees drained Africans of their blood may reveal more than the vivid imagination of their narrators; they disclose the concerns and anxieties of people at a specific time and place.
African Studies Seminar series. Paper presented 16 August 1993
Keywords: Urban folklore. Africa; Blood. Collection and preservation. Folklore; Kidnapping. Africa. Folklore; Fire fighters. Africa. Folklore; Motor vehicles. Africa. Folklore; Labor. Africa. Folklore